Development of pupils’ cognitive abilities - Sičiūnienė, Viktorija (Lietuvos matematikos rinkinys, 2018)
The article analyzes the situation of the development of cognitive abilities in Lithuania. It alsointroduces Revised Bloom Taxonomy and its application experiences in developed world countries.The emphasis is placed on the importance of applying Bloom-taxonomy to all levels of the educationsystem in order to achieve higher student achievement.
Keywords: blooms taxonomy; cognitive domain; mathematics education; national standards